EFL teachers' online teaching in rural schools during the COVID-19 pandemic: Stories from Indonesia - I Putu Indra Kusuma (Universitas Syiah Kuala, 2022)
The implementation of online English instruction in remote areas during the COVID-19 pandemic, which mandates school closures, remains unknown, especially given these areas' reputation for inadequate educational facilities. Additionally, the preparations, implementation, and challenges experienced by English as a Foreign Language (henceforth, EFL) teachers in rural areas remain unclear. This study therefore aimed at exploring the experiences of EFL teachers in rural areas on (1) their readiness for conducting online teaching, (2) their implementation of online teaching, and (3) the challenges during the implementation of online teaching due to the COVID-19 pandemic. The research was conducted in Indonesia with eight English teachers in rural schools. This study was a qualitative study that employed a phenomenological study approach and used semi-structured interviews to collect the data. The findings indicate that EFL teachers, during this pandemic time, were able to conduct fully online English teaching because they possessed sufficient knowledge of English instruction using technology. Additionally, these teachers might leverage various technologies and adapt those tools to transform their usual face-to-face English instruction into online instruction. Nonetheless, these teachers in rural schools frequently encountered challenges with internet connectivity, student-owned technology devices, student enthusiasm, and student netiquette when enrolling in online English teaching. Additionally, this article discusses some practical considerations for implementing online English teaching during a pandemic.